2020
DOI: 10.1002/ps.5861
|View full text |Cite
|
Sign up to set email alerts
|

The potential distribution and dynamics of important vectors Culex pipiens pallens and Culex pipiens quinquefasciatus in China under climate change scenarios: an ecological niche modelling approach

Abstract: BACKGROUNDIntense studies have been carried out on the effects of climate change on vector‐borne diseases and vectors. Culex pipiens pallens and Culex pipiens quinquefasciatus are two medically concerned mosquito species in temperate and tropical areas, which serve as important disease‐transmitting pests of a variety of diseases. The ongoing geographical expansion of these mosquitoes has brought an increasing threat to public health.RESULTSBased on mosquito occurrence records and high‐resolution environmental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 78 publications
1
25
0
Order By: Relevance
“…Previous studies have suggested that the spatial distribution of malaria, which is transmitted by Anopheles mosquitoes, has shifted toward higher altitudes [7], and that the length of its transmission season has increased in highland regions [8,9]. Modeling studies carried out in China and Canada have shown that the geographical range of Culex, which is responsible for the transmission of West Nile fever and Japanese encephalitis virus, will shift northward under future climate scenarios [10,11]. Species of the genus Aedes that are vectors of dengue and Zika viruses are also projected to spread globally and cause local outbreaks of these diseases in non-endemic areas [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have suggested that the spatial distribution of malaria, which is transmitted by Anopheles mosquitoes, has shifted toward higher altitudes [7], and that the length of its transmission season has increased in highland regions [8,9]. Modeling studies carried out in China and Canada have shown that the geographical range of Culex, which is responsible for the transmission of West Nile fever and Japanese encephalitis virus, will shift northward under future climate scenarios [10,11]. Species of the genus Aedes that are vectors of dengue and Zika viruses are also projected to spread globally and cause local outbreaks of these diseases in non-endemic areas [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…To avoid confounding effects caused by spatial stratified heterogeneity (SSH), we calculated the q ‐statistic by using the GeoDetector (http://geodetector.cn/) software 21,22 . County level occurrences were paired with integer codes representing the provincial level administrative regions to which they belong 23,24 . The q ‐statistic tests indicate that no significant SSH exists in the samples of Z. mays ( q = 0.092; P = 1.000), R. maidis ( q = 0.116; P = 0.999), or ScMV ( q = 0.365; P = 0.795).…”
Section: Methodsmentioning
confidence: 99%
“…pipiens (Gangoso et al., 2020) (see Sánchez‐Gómez et al., 2017 for another approach). Furthermore, in most cases the occurrence data was restricted to the records occurring in the area of interest (Adham et al., 2019; Baak‐Baak et al., 2017; Ben Hassine et al., 2019; Conley et al., 2014; Cunze et al., 2016; Gangoso et al., 2020; García‐Bocanegra et al., 2018; Hesami et al., 2019; Kalan et al., 2017; Koch et al., 2016; Larson et al., 2010; Liu et al., 2020; Medley, 2010; Melaun et al., 2015; Moua et al., 2021; Mughini‐Gras et al., 2014; Outammassine et al., 2021; Peach et al., 2019; Peterson et al., 2008; Sallam et al., 2016, 2017; Wiese et al., 2019), thus not considering the entire niche occupied by the species to be model as recommended (Cunze et al., 2020), and probably underestimating the resulting distribution.…”
Section: Introductionmentioning
confidence: 99%
“…Concerning WNV, most of the studies using niche model techniques has focused on the distribution of its vectors, but seldom considered the distribution of the virus or the disease system as a whole (i.e. Adham et al, 2019;Baak-Baak et al, 2017;Conley et al, 2014;Cunze et al, 2016Cunze et al, , 2020Figueroa et al, 2020;Filatov, 2017;Hesami et al, 2019;Ibáñez-Justicia et al, 2020;Kalan et al, 2017;Koch et al, 2016;Larson et al, 2010;Liu et al, 2020;Medley, 2010;Melaun et al, 2015;Moua et al, 2021;Mughini-Gras et al, 2014;Peach et al, 2019;Sallam et al, 2016Sallam et al, , 2017Samy et al, 2016;Wiese et al, 2019;but see Ben Hassine et al, 2019 andPeterson et al, 2008). The former is particularly evident in the Iberian Peninsula, where only a couple of studies considered niche modelling techniques either at a very local level (García-Bocanegra et al, 2018) or for modelling the distribution of its main vector, Cx.…”
mentioning
confidence: 99%